A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

A systems modelling approach to predict biological responses to extreme heat - Daniel W.A. Noble; Margaret M. Mayfield; Ary A. Hoffmann; Zhong-Hua Chen; Steven J. Lade; Xuemei Bai; Danielle A. Way; Belinda E. Medlyn; Owen K. Atkin; Adrienne B. Nicotra; James M. Cook; Brajesh K. Singh; et al. (Trends in Ecology & Evolution, 2026)

Integrating the Microbiome Into Infection Ecology and Evolution in Wild Animals - Jingdi Li; Ian Will; Luís M. Silva; Tommy J. Travers‐Cook; Paradyse E. Blackwood; Kayla C. King (Molecular Ecology, 2026)
Parasites are a ubiquitous force in nature threatening wildlife populations and ecosystems. Interactions between hosts and their parasites are impacted by host‐associated microbiomes, which are essential for host development, physiology and immunity. We synthesise current understanding of the ecological interactions between host microbiomes and parasites, ranging from competitive to facilitative, and explore their potential evolutionary consequences for parasite virulence and transmission in the wild. We highlight recent mechanistic insights that support integrating a microbiome perspective into wildlife parasitology, with examples across diverse animal taxa including amphibians, bats, insects and corals, particularly within the context of climate change. Adopting such a holistic approach can open new avenues whereby host microbial shifts can be used to predict and mitigate infectious diseases in wild populations. Finally, we propose a conceptual framework to guide future research on microbiome‐parasite–host interactions, aiming to better reflect natural ecological complexities and advance both fundamental understanding and conservation applications.

Expanding Monitoring Capacity for Potential Invasive Species in Arctic Canada With Environmental DNA Metabarcoding - Elizabeth Boyse; Melody S. Clark; Ian M. Carr; Alison J. Cook; Philippe Archambault; Jean E. Holloway; Zhewen Luo; Michael Milton; Mathieu Roy; Jackie Dawson; Victoria L. Peck (Global Change Biology, 2025)
To date, environmental conditions have been enough to act as an effective barrier to prevent non‐indigenous species from arriving and establishing in Arctic Canada. However, rapidly changing climatic conditions are creating more suitable habitats for non‐indigenous species to potentially establish and become invasive. Concurrently, shipping traffic in parts of Arctic Canada has increased by over 250% since 1990, providing an effective vector for transporting non‐indigenous species to the region. Arctic Canada has been historically undersampled, so Arctic biota inventories are incomplete, hampering efforts to establish if a species is new to the region (and potentially invasive) or newly discovered. In this study, we utilize environmental DNA (eDNA) metabarcoding and ships of opportunity to assess eukaryotic community composition and potential invasives along one of the busiest shipping routes, the Northwest Passage. One liter seawater samples were collected in triplicate at 27 locations, targeting touristic hotspots frequently visited by passenger vessels. Eukaryotic DNA was amplified from the 18S rRNA V9 and COI regions, resulting in 126 unique Amplicon Sequence Variants (ASVs) detected with COI and 391 ASVs with 18S, providing an important snapshot of current community composition. Copepods, dinoflagellates, and diatoms were the most abundant taxonomic groups, correlating well with previous net sampler surveys, validating the efficacy of eDNA for biodiversity surveillance. We also report the first detections of a prolific invasive species, the bay barnacle ( Amphibalanus improvisus ), in Arctic Canada. Further work is currently in progress to establish whether these detections represent transient barnacle larvae or sessile adults capable of recruiting and reproducing. Our study demonstrates the utility of eDNA for the detection of non‐indigenous species in a data‐poor area, which, if combined with citizen science initiatives and local communities, could provide a vital monitoring tool for the detection of new invasives in this rapidly changing area.

Utilization and outcomes of serial cervical cancer screening in a National Breast and Cervical Cancer Early Detection Program (NBCCEDP) in a non-Medicaid expansion state - Rubina Ratnaparkhi; Ahmed Ismail; Hope Krebill; Ian Cook; Melissa Javellana; Andrea Jewell; Lori Spoozak; Amanda Emerson; Megha Ramaswamy; Elizabeth Calhoun; Dinesh Pal Mudaranthakam (Cancer Causes & Control, 2025)

Threat assessment for Pacific sand lance (Ammodytes personatus) in the Salish Sea - Jacqueline R. Huard; Victoria Hemming; Matthew R. Baker; Jennifer Blancard; Ian Bruce; Sarah Cook; Gail K. Davoren; Phillip Dionne; Virginia East; J. Mark Hipfner; Nicola R. Houtman; Brian A. Koval; et al. (Frontiers in Marine Science, 2024)
Like many forage fish species, Pacific sand lance ( Ammodytes personatus ) play a key role in nearshore marine ecosystems as an important prey source for a diverse array of predators in the northeastern Pacific. However, the primary threats to Pacific sand lance and their habitat are poorly defined due to a lack of systematic data. Crucial information needed to assess their population status is also lacking including basic knowledge of their local and regional abundance and distribution. Sand lance are currently listed as ‘not evaluated’ under the IUCN red list and they have not been assessed by US and Canadian agencies. This hampers management and policy efforts focused on their conservation. To address this knowledge gap, we conducted a three-part, structured expert elicitation to assess the vulnerability of Salish Sea sand lance populations. Experts were asked to list and rank key threats to Salish Sea sand lance and/or their habitat, to further quantify the vulnerability of sand lance to identified threats using a vulnerability matrix, and to predict the population trajectory in 25 years from today. Impacts associated with climate change (e.g. sea level rise, sea temperature rise, ocean acidification, and extreme weather) consistently ranked high as threats of concern in the ranking exercise and quantified vulnerability scores. Nearly every expert predicted the population will have declined from current levels in 25 years. These results suggest sand lance face numerous threats and may be in decline under current conditions. This research provides vital information about which threats pose the greatest risk to the long-term health of sand lance populations and their habitat. Managers can use this information to prioritize which threats to address. Future research to reliably quantify population size, better understand the roles of natural and anthropogenic impacts, and to identify the most cost-effective actions to mitigate multiple threats, is recommended.

The value of seabird foraging ranges as a tool to investigate potential interactions with offshore wind farms - Ian D. Woodward; Chris B. Thaxter; Ellie Owen; Mark Bolton; Robin M. Ward; Aonghais S.C.P. Cook (Ocean & Coastal Management, 2024)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

Moderate D/H ratios in methane ice on Eris and Makemake as evidence of hydrothermal or metamorphic processes in their interiors: Geochemical analysis - Christopher R. Glein; William M. Grundy; Jonathan I. Lunine; Ian Wong; Silvia Protopapa; Noemi Pinilla-Alonso; John A. Stansberry; Bryan J. Holler; Jason C. Cook; Ana Carolina Souza-Feliciano (Icarus, 2024)

The distinctive weathering crust habitat of a High Arctic glacier comprises discrete microbial micro‐habitats - Sara M. E. Rassner; Joseph M. Cook; Andrew C. Mitchell; Ian T. Stevens; Tristram D. L. Irvine‐Fynn; Andrew J. Hodson; Arwyn Edwards (Environmental Microbiology, 2024)
Sunlight penetrates the ice surfaces of glaciers and ice sheets, forming a water‐bearing porous ice matrix known as the weathering crust. This crust is home to a significant microbial community. Despite the potential implications of microbial processes in the weathering crust for glacial melting, biogeochemical cycles, and downstream ecosystems, there have been few explorations of its microbial communities. In our study, we used 16S rRNA gene sequencing and shotgun metagenomics of a Svalbard glacier surface catchment to characterise the microbial communities within the weathering crust, their origins and destinies, and the functional potential of the weathering crust metagenome. Our findings reveal that the bacterial community in the weathering crust is distinct from those in upstream and downstream habitats. However, it comprises two separate micro‐habitats, each with different taxa and functional categories. The interstitial porewater is dominated by Polaromonas , influenced by the transfer of snowmelt, and exported via meltwater channels. In contrast, the ice matrix is dominated by Hymenobacter , and its metagenome exhibits a diverse range of functional adaptations. Given that the global weathering crust area and the subsequent release of microbes from it are strongly responsive to climate projections for the rest of the century, our results underscore the pressing need to integrate the microbiome of the weathering crust with other communities and processes in glacial ecosystems.

Simulating carbon accumulation and loss in the central Congo peatlands - Dylan M. Young; Andy J. Baird; Paul J. Morris; Greta C. Dargie; Y. Emmanuel Mampouya Wenina; Mackline Mbemba; Arnoud Boom; Peter Cook; Richard Betts; Eleanor Burke; Yannick E. Bocko; Sarah Chadburn; et al. (Global Change Biology, 2023)
Peatlands of the central Congo Basin have accumulated carbon over millennia. They currently store some 29 billion tonnes of carbon in peat. However, our understanding of the controls on peat carbon accumulation and loss and the vulnerability of this stored carbon to climate change is in its infancy. Here we present a new model of tropical peatland development, DigiBog_Congo, that we use to simulate peat carbon accumulation and loss in a rain‐fed interfluvial peatland that began forming ~20,000 calendar years Before Present (cal. yr BP, where ‘present’ is 1950 CE). Overall, the simulated age‐depth curve is in good agreement with palaeoenvironmental reconstructions derived from a peat core at the same location as our model simulation. We find two key controls on long‐term peat accumulation: water at the peat surface (surface wetness) and the very slow anoxic decay of recalcitrant material. Our main simulation shows that between the Late Glacial and early Holocene there were several multidecadal periods where net peat and carbon gain alternated with net loss. Later, a climatic dry phase beginning ~5200 cal. yr BP caused the peatland to become a long‐term carbon source from ~3975 to 900 cal. yr BP. Peat as old as ~7000 cal. yr BP was decomposed before the peatland's surface became wetter again, suggesting that changes in rainfall alone were sufficient to cause a catastrophic loss of peat carbon lasting thousands of years. During this time, 6.4 m of the column of peat was lost, resulting in 57% of the simulated carbon stock being released. Our study provides an approach to understanding the future impact of climate change and potential land‐use change on this vulnerable store of carbon.

Investigating slow-moving shallow soil landslides using Sentinel-1 InSAR data in Gisborne, New Zealand - Matthew E. Cook; Martin S. Brook; Ian J. Hamling; Murry Cave; Jon F. Tunnicliffe; Rachel Holley (Landslides, 2023)
Landslides are widespread geomorphological features on the North Island of New Zealand, where they represent one of the primary landscape-forming processes. This study focuses on the steepland terrain surrounding Gisborne, a city located on the east coast of the North Island, at the Hikurangi subduction margin. This terrain consists of young, weak, sedimentary rocks and soils; the most common modes of slope failures are soil creep, slides and flows in shallow, clay-rich soil and regolith, triggered by heavy rainfall. Based on observational data from Sentinel-1 imagery, this study leverages results from interferometric synthetic aperture radar (InSAR) processing to reveal the distribution of deformation across Gisborne’s steepland periphery from January 2016 to December 2021. Velocities in the line of sight were obtained from the stack of interferograms and projected along the direction of maximum slope, to extract the true displacement on the slopes. The ascending and descending data sets were combined to reveal the vertical and horizontal components of the deformation. The results were combined with a regional LiDAR data set, aerial imagery and field observations to delineate areas of slope deformation. Finally, slope deformation time series data was compared with rainfall records to identify seasonal changes, due to shrinking and swelling of expansive soils. Although the InSAR displacement data contains some noise, results could be used to identify 132 unstable slopes within the study area, caused by soil creep and earthflows. Also, the shrink-swell of expansive soils causes a seasonal pattern of displacements, which varied by 10–20 mm/year between Austral winter and summer, strongly correlated to rainfall.

Engineering geomorphological and InSAR investigation of an urban landslide, Gisborne, New Zealand - Matthew E. Cook; Martin S. Brook; Ian J. Hamling; Murry Cave; Jon F. Tunnicliffe; Rachel Holley; David J. Alama (Landslides, 2022)
The East Coast region of New Zealand has some of the highest erosion rates in the world, due to its proximity to an active plate boundary, susceptibility to high-intensity storms and steep terrain underlain by young soft sedimentary rock and soil. In the city of Gisborne, expansion of residential blocks into steeper terrain in peri-urban areas has required improved capacity for the characterisation and monitoring of slope stability. Landslides have affected several properties and have destroyed infrastructure. Slope failure commonly occurs during heavy rainfall events when slow-moving retrogressive slides transition into earthflows and mudflows. In this study, we used in situ sampling and testing methods combined with remote sensing techniques to provide an understanding of the pre-failure and post-failure behaviour of an urban landslide in Gisborne. High-resolution aerial imagery, unmanned aerial vehicle imagery and light detection and ranging data revealed slope morphology and contours of prehistoric failures in the area, and highlighted the more recent impacts of deforestation on slope stability. Furthermore, Sentinel-1 InSAR analysis determined that gradual deformation began in 2017, following two ex-tropical cyclone events. Deformation downslope continued until an initial failure in July 2020. Following that event, some parts of the slope proceeded to accelerate, leading to a further reactivation event in November 2021, following heavy rainfall. During this November 2021 event, average line of sight velocities ranged from −7.9 to −11.2 mm/year, and deformation rates in the vertical direction (related to rotational slumping) averaged −11.2 to −11.9 mm/year, consistent with field observations.

Tracking the Rates and Mechanisms of Canopy Damage and Recovery Following Hurricane Maria Using Multitemporal Lidar Data - Veronika Leitold; Douglas C. Morton; Sebastián Martinuzzi; Ian Paynter; María Uriarte; Michael Keller; António Ferraz; Bruce D. Cook; Lawrence A. Corp; Grizelle González (Ecosystems, 2022)

Epiphytic fungal communities vary by substrate type and at submetre spatial scales - Kel Cook; Jyotsna Sharma; Andrew D. Taylor; Ian Herriott; D. Lee Taylor (Molecular Ecology, 2022)
Fungal species have numerous important environmental functions. Where these functions occur will depend on how fungi are spatially distributed, but the spatial structures of fungal communities are largely unknown, especially in understudied hyperdiverse tropical tree canopy systems. Here we explore fungal communities in a Costa Rican tropical rainforest canopy, with a focus on local‐scale spatial structure and substrate specificity of fungi. Samples of ~1 cm 3 were collected from 135 points along five adjacent tree branches, with intersample distances from 1 to 800 cm, and dissected into four substrates: outer host tree bark, inner bark, dead bryophytes and living bryophytes. We sequenced the ITS2 region to characterize total fungal communities. Fungal community composition and diversity varied among substrate types, even when multiple substrates were in direct contact. Fungi were most diverse in living bryophytes, with 39% of all operational taxonomic units (OTUs) found exclusively in this substrate, and the least diverse in inner bark. Fungal communities had significant positive spatial autocorrelation and distance decay of similarity only at distances less than 1 m. Similarity among samples declined by half in less than 10 cm, and even at these short distances, similarities were low with few OTUs shared among samples. These results indicate that community turnover is high and occurs at very small spatial scales, with any two locations sharing very few fungi in common. High heterogeneity of fungal communities in space and among substrates may have implications for the distributions, population dynamics and diversity of other tree canopy organisms, including epiphytic plants.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Nitrogen and oxygen isotopomeric constraints on the sources of nitrous oxide and the role of submarine groundwater discharge in a temperate eutrophic salt‐wedge estuary - Wei Wen Wong; Moritz F. Lehmann; Thomas Kuhn; Caitlin Frame; Seng Chee Poh; Ian Cartwright; Perran L.M. Cook (Limnology and Oceanography, 2021)
Estuaries have been identified as sources of nitrous oxide (N 2 O) emissions to the atmosphere but questions remain as to which production pathway(s) govern the oversaturation of N 2 O observed in most estuaries worldwide. Here, we use a suite of nitrate and N 2 O isotopes, as well as the 15 N site preference signatures of N 2 O to assess (1) the relative importance of different N 2 O production pathways in a eutrophic groundwater‐impacted salt‐wedge estuary and the aquifers underlying the estuary and (2) the influence of groundwater input on the overall N 2 O saturation in the estuary. This is one of the few studies to examine the effect of groundwater–surface water interaction on N 2 O cycling using N 2 O isotopes. The site preference values of N 2 O in the deep aquifer below the estuary were distinctive (83‰ ± 25‰) and were much higher than in either surface water (21‰ ± 6‰) or shallow groundwater (44‰ ± 8‰), suggesting the influence of multiple biotic and/or abiotic processes which proceed through multiple cycles, and/or the occurrence of a yet unidentified N 2 O production pathway. Isotope endmember considerations revealed that nitrifier‐denitrification was the major N 2 O production pathway within the shallow aquifer whereas within the estuarine water column, N 2 O saturation was governed by chemodenitrification and discharge of N 2 O‐laden submarine groundwater. Our study not only emphasizes the substantial, yet often underappreciated role of submarine groundwater discharge in estuarine N 2 O budgets, but also highlights the need to reevaluate the importance of the noncanonical denitrification pathways (i.e., chemodenitrification and nitrifier‐denitrification) in controlling the overall N 2 O production from estuarine and groundwater environments.

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Correction to: Amyloid Precursor Protein Mediates Neuronal Protection from Rotenone Toxicity - Kathryn Cimdins; Hayley S. Waugh; Vicki Chrysostomou; M. Isabel G. Lopez Sanchez; Vanessa A. Johanssen; Mark J. Cook; Jonathan G. Crowston; Andrew F. Hill; James A. Duce; Ashley I. Bush; Ian A. Trounce (Molecular Neurobiology, 2019)

Amyloid Precursor Protein Mediates Neuronal Protection from Rotenone Toxicity - Kathryn Cimdins; Hayley S. Waugh; Vicki Chrysostomou; M. Isabel G. Lopez Sanchez; Vanessa A. Johannsen; Mark J. Cook; Jonathan G. Crowston; Andrew F. Hill; James A. Duce; Ashley I. Bush; Ian A. Trounce (Molecular Neurobiology, 2019)

Standardized reporting of the costs of management interventions for biodiversity conservation - Gwenllian D. Iacona; William J. Sutherland; Bonnie Mappin; Vanessa M. Adams; Paul R. Armsworth; Tim Coleshaw; Carly Cook; Ian Craigie; Lynn V. Dicks; James A. Fitzsimons; Jennifer McGowan; Andrew J. Plumptre; et al. (Conservation Biology, 2018)
Effective conservation management interventions must combat threats and deliver benefits at costs that can be achieved within limited budgets. Considerable effort has focused on measuring the potential benefits of conservation interventions, but explicit quantification of the financial costs of implementation is rare. Even when costs have been quantified, haphazard and inconsistent reporting means published values are difficult to interpret. This reporting deficiency hinders progress toward a collective understanding of the financial costs of management interventions across projects and thus limits the ability to identify efficient solutions to conservation problems or attract adequate funding. We devised a standardized approach to describing financial costs reported for conservation interventions. The standards call for researchers and practitioners to describe the objective and outcome, context and methods, and scale of costed interventions, and to state which categories of costs are included and the currency and date for reported costs. These standards aim to provide enough contextual information that readers and future users can interpret the cost data appropriately. We suggest these standards be adopted by major conservation organizations, conservation science institutions, and journals so that cost reporting is comparable among studies. This would support shared learning and enhance the ability to identify and perform cost‐effective conservation.

Aeromagnetic Surveying with a Rotary-Wing Unmanned Aircraft System: A Case Study from a Zinc Deposit in Nash Creek, New Brunswick, Canada - Michael Cunningham; Claire Samson; Alan Wood; Ian Cook (Pure and Applied Geophysics, 2018)

Under what circumstances does the capture and tagging of wild Atlantic salmon Salmo salar smolts affect probability of return as adults? - William D. Riley; Anton T. Ibbotson; Stephen D. Gregory; Ian C. Russell; Rasmus B. Lauridsen; William R. C. Beaumont; Alastair C. Cook; David L. Maxwell (Journal of Fish Biology, 2018)
Adult return rates for wild Atlantic salmon Salmo salar smolts captured in a rotary screw trap and tagged with coded wire (CW) tags were compared with a control group, using detections from passive integrated transponder (PIT) antennae systems over 7 years in a small chalk stream in southern England, U.K. Compared with control smolts, capture and CW‐tagging of experimental smolts affected detected return rates only under certain conditions, with a decreased return probability for smolts caught and tagged following mild winter river temperature anomalies and during the night. Similarly, analysis of the experimental smolts revealed that capture and CW‐tagging following mild winters decreased their probability of return as adults. There were also marginal positive effects of length at PIT‐tagging as parr and length at CW‐tagging as smolts, on individual probability of return as adult. The results support the hypothesis that the effect of procedures involving the capture and tagging of migrating wild S. salar smolts will vary with the circumstances under which they are performed. The implications of the findings are considered in the context of ongoing investigations to derive and report marine return rates for S. salar in support of national and international stock assessments and in developing best practice.

China’s urbanization in 1949–2015: Processes and driving forces - Chaolin Gu; Lingqian Hu; Ian G. Cook (Chinese Geographical Science, 2017)

Evaluation of Non-destructive Molecular Diagnostics for the Detection of Neoparamoeba perurans - Jamie K. Downes; Megan L. Rigby; Richard S. Taylor; Ben T. Maynard; Eugene MacCarthy; Ian O'Connor; Mar Marcos-Lopez; Hamish D. Rodger; Evelyn Collins; Neil M. Ruane; Mathew T. Cook (Frontiers in Marine Science, 2017)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Antidepressant treatment history and drug-placebo separation in a placebo-controlled trial in major depressive disorder - Aimee M. Hunter; Ian A. Cook; Molly Tartter; Simi K. Sharma; Gregory D. Disse; Andrew F. Leuchter (Psychopharmacology, 2015)

A characterization of volatile organic compounds and secondary organic aerosol at a mountain site in the Southeastern United States - Michael Link; Yong Zhou; Brett Taubman; James Sherman; Hadi Morrow; Ian Krintz; Luke Robertson; Ryan Cook; Justine Stocks; Matthew West; Barkley C. Sive (Journal of Atmospheric Chemistry, 2015)

Sources and fate of nitrate in a groundwater‐fed estuary elucidated using stable isotope ratios of nitrogen and oxygen - Wei Wen Wong; Michael R. Grace; Ian Cartwright; Perran L. M. Cook (Limnology and Oceanography, 2014)
We used δ 15 N‐nitrate (NO − 3 ) and δ 18 O‐NO − 3 to unravel the provenance and fate of NO − 3 in a groundwater‐fed estuary. A total of 13 monthly and two time series surveys were undertaken in the Werribee River estuary near Melbourne, Australia. The different survey timescales provided a comprehensive evaluation of the hydrological effects on the biogeochemistry of NO − 3 , which accounted for tidal variability and episodic runoff events. The distribution of δ 15 N and δ 18 O of the estuarine NO − 3 along a mixing line between shallow and deep groundwater provided strong evidence for the predominance of groundwater‐derived NO − 3 in the estuary. During dry periods when water residence time in the estuary was extended, shallow groundwater contributed 60% to 76% of the NO − 3 (calculated from δ 15 N‐NO − 3 and δ 18 O‐NO − 3 ) to the estuary, and assimilation removed ∼ 70% of this groundwater‐derived NO − 3 . During wet periods, deep groundwater provided more (62%) NO − 3 than shallow groundwater, and there was no indication of NO − 3 consumption. Occasional sources of NO − 3 , which were also reflected by their δ 15 N‐NO − 3 and δ 18 O‐NO − 3 values, included NO − 3 from nitrification and sewage‐derived NO − 3 particularly at the bay entrance to the estuary. Greater emphasis should be placed upon the role of groundwater as a substantial NO − 3 end member when assessing NO − 3 biogeochemistry using methods relying on the dual isotopic composition of NO − 3 .

Pore‐water exchange driven by tidal pumping causes alkalinity export in two intertidal inlets - Peter A. Faber; Victor Evrard; Ryan J. Woodland; Ian C. Cartwright; Perran L. M. Cook (Limnology and Oceanography, 2014)
Carbon (C) and alkalinity export from two adjacent intertidal inlets with different terrestrial inputs was investigated. One inlet receives a small creek from an agriculturally dominated catchment, leading to the input of terrestrially sourced material, whereas the other is relatively isolated from terrestrial inputs. Using time‐series measurements, we calculated the total advective exchange of dissolved organic C (DOC; 0–25 mmol m ‒2 d ‒1 ), dissolved inorganic C (DIC; 130–450 mmol m ‒2 d ‒1 ), total alkalinity (TA; 46–310 mmol m ‒ d ‒1 ), and the nutrients nitrate (1.0–1.1 mmol m ‒2 d ‒1 ), ammonia (0.0043–0.10 mmol m ‒2 d ‒1 ), and phosphorus (0.016–0.25 mmol m ‒2 d ‒1 ). Radon‐222 ( 222 Rn) data indicated that pore‐water exchange played an important part in controlling C export from the sediment as an advective flux. The residence time of pore water within both inlets was ~ 6.6–7.4 h, indicating that pore‐water exchange is driven by tidal pumping. The inlet with the greater amount of terrestrial inputs exported much more TA (310 vs. 46 mmol m ‒2 d ‒1 ), suggesting that the extent of land‐to‐sea connectivity influences how C is exported. We hypothesize that this is due to the increased input of iron (Fe) from terrestrial sources, which fosters net TA production through the burial of reduced sulfur species as Fe sulfides. A simple mass balance showed that the TA fluxes observed over 24 h were higher than could be sustained continuously with Fe input from the catchment (0.49 mmol Fe m ‒2 d ‒1 ), meaning that the observed TA fluxes could not be sustained on long timescales. It is most likely that there are periods of net reduction and net oxidation in response to wave action and calm conditions, highlighting the importance of long‐term monitoring over different seasons and weather patterns to obtain representative budgets.

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Dynamics of groundwater‐derived nitrate and nitrous oxide in a tidal estuary from radon mass balance modeling - Wei Wen Wong; Michael R. Grace; Ian Cartwright; M. Bayani Cardenas; Peter B. Zamora; Perran L. M. Cook (Limnology and Oceanography, 2013)
We monitored submarine groundwater discharge (SGD) into the Werribee Estuary, Australia, using both chemical and physical methods. SGD occurred at hotspots where 222 Rn persisted through a 12 month survey period. A significant correlation between 222 Rn and ( r 2 = 0.8, p 222 Rn and N 2 O ( r 2 = 0.6, p 222 Rn hotspot, and much higher and N 2 O concentrations in groundwater relative to surface water suggest that elevated and N 2 O concentrations in the estuary were derived from SGD. Two sampling campaigns over 24 h revealed that variations of 222 Rn,, and N 2 O were controlled by tide‐induced hydraulic‐head gradient fluctuations and, possibly to a much lesser extent, by tidal pumping and density‐driven convection. A two‐box 222 Rn mass‐balance model was used to calculate the rate of SGD into two different layers across the pycnocline of the estuary. A higher total groundwater discharge rate of 0.12 ± 0.09 m d −1 was observed in the surface layer during ebb tide compared with 0.10 ± 0.08 m d −1 during flood tide. Fluxes of groundwater‐derived and N 2 O were higher than the riverine flux at baseflow by more than 30 fold and 20 fold, respectively. SGD derived fluxes exceeded the mean annual riverine and TN fluxes by a factor of ∼ 5 and ∼ 3 respectively. SGD‐derived N 2 O fluxes were 170 µmol m −2 d −1 , which are among the highest N 2 O fluxes observed in estuaries.

Brain Electrical Source Differences between Depressed Subjects and Healthy Controls - Alexander S. Korb; Ian A. Cook; Aimee M. Hunter; Andrew F. Leuchter (Brain Topography, 2008)

ORIGINAL ARTICLE: Human impact on an island ecosystem: pollen data from Sandoy, Faroe Islands - Ian T. Lawson; Kevin J. Edwards; Mike J. Church; Anthony J. Newton; Gordon T. Cook; Freddy J. Gathorne‐Hardy; Andrew J. Dugmore (Journal of Biogeography, 2008)
Aim To investigate the form and dynamics of ecosystems on an isolated island in the North Atlantic before human settlement in the first millennium ad , and the effects of human activities thereafter. Location The island of Sandoy, Faroes (61°50′ N, 6°45′ W). Methods Two sequences of lake sediments and one of peat were studied using pollen analysis and sedimentological techniques. Age models were constructed on the basis of radiocarbon dating and, in one case, tephrochronology. The data were analysed statistically and compared with existing data from the region. Results The pollen data indicate that early Holocene vegetation consisted of fell‐field communities probably growing on raw, skeletal soils. These communities gave way to grass‐ and sedge‐dominated communities, which in turn were largely replaced by dwarf shrub‐dominated blanket mire communities well before the first arrival of humans. There is evidence for episodic soil erosion, particularly in the uplands. Changes in the records attributable to human impact are minor in comparison with many other situations in the North Atlantic margins, and with certain published sequences from elsewhere in the Faroes. They include: (1) the appearance of cereal pollen and charcoal, (2) an expansion of ruderal taxa, (3) a decline in certain taxa, notably Juniperus communis and Filipendula ulmaria , and (4) a renewed increase in rates of upland soil erosion. The reliability of palaeoecological inferences drawn from these sites, and more generally from sites in similar unforested situations, is discussed. Main conclusions The subdued amplitude of palynological and sedimentological responses to settlement at these sites can be explained partly in terms of their location and partly in terms of the sensitivity of different parts of the ecosystem to human activities. This study is important in establishing that the imposition of people on the pristine environment of Sandoy, while far from negligible, especially in the immediate vicinity of early farms and at high altitudes, had relatively little ecological impact in many parts of the landscape.

Pretreatment neurophysiological and clinical characteristics of placebo responders in treatment trials for major depression - Andrew F. Leuchter; Melinda Morgan; Ian A. Cook; Jennifer Dunkin; Michelle Abrams; Elise Witte (Psychopharmacology, 2004)

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. III. Colonization by birds - Clinton Schipper; Mike Shanahan; Simon Cook; Ian W. B. Thornton (Journal of Biogeography, 2001)
Location, Aim Long Island, 55 km north of New Guinea, erupted explosively in the seventeenth century and has been recolonized by animals and plants. Effectively in 1968, an island, Motmot, emerged from Long's 13 km‐diameter fresh‐water caldera lake, about 4 km from the nearest shore. A nested pair of colonization sequences is thus available for study. Long Island has been recolonized by birds, and Motmot has been colonized, presumably from the surrounding ring of Long Island. In order to monitor further colonization of Long Island following bird surveys in 1933 and 1972, and to survey the birds of Motmot, Motmot and the western parts of Long were visited for 15 days in 1999. Results In the last 66 years one species probably has become extinct; in the past 27 years three species have colonized and three, present in 1972, were not recorded in 1999. We assess the present number of nonmigrant land bird species as fifty. On Motmot, we recorded eight species, three breeding, and found two more only as prey remains (three raptor species were seen on the island). Main conclusions Long Island's avifauna still has youthful features. Species with good colonizing ability predominate, and there are no island‐endemic subspecies. There is a persistently high proportion of supertramps; none of the ten supertramps has been replaced by later‐colonizing ‘high‐S' species. A quasi‐equilibrium of about fifty species, fourteen fewer than the predicted equilibrium number for the island, has persisted for at least seven decades and may be seen as that appropriate to the present prolonged stage of Long's floral and vegetational development. Compared with the younger avifauna of Krakatau, Long's avifauna has a higher proportion of nectarivores, predators of large invertebrates and small vertebrates, and ground‐foraging insectivore‐herbivores, and a lower proportion of the insectivore‐frugivore guild. Motmot's small avifauna consists predominantly of species obtaining subsistence from outside the island.

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. III. Colonization by birds - Clinton Schipper; Mike Shanahan; Simon Cook; Ian W. B. Thornton (Journal of Biogeography, 2001)

Three new species of Apheviderulix gen. nov. and proposal of Apheviderulicidae fam. nov. (Acari: Hydrachnidia: Eylaoidea) - Reinhard Gerecke; Ian M. Smith; David R. Cook (Hydrobiologia, 1999)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)